The Effect of Social Media Marketing, eWOM, Brand Awareness, and Brand Image on Purchase Intention - Putra, Trio; Secapramana, Laurentia Verina Halim (Dinasti International Journal of Management Science, 2025)
This study aims to analyze the influence of social media marketing, eWOM, brand awareness, and brand image on purchase intention among @erigostore consumers. Data were collected through a survey with 180 respondents from an online questionnaire. Respondents of this study were Erigo consumers who had purchased within the last 6 months, those consumers also had social media and followed the @erigostore social media account, and consumers who had read or commented on Erigo products. This study used a Structural Equation Modeling (SEM) approach using the AMOS application to analyze the data. The results of this study indicate that social media marketing has a positive and significant influence on brand awareness, brand image, and purchase intention, which confirms the strategic role of social media in shaping consumer perceptions and behavior. Conversely, eWOM was found to have a negative and significant effect on brand image and purchase intention, and had no significant effect on brand awareness, which indicates that the spread of negative information online can damage brand image and reduce purchase intention even though the level of brand awareness remains high. In addition, brand awareness has a positive but insignificant influence on purchase intention, while brand image is proven to have a positive and significant influence.